Kicking performance and muscular strength parameters with dominant and nondominant lower limbs in brazilian elite professional futsal players - Palucci Vieira, L. H.; de Souza Serenza, F.; de Andrade, V. L.; de Paula Oliveira, L.; Pamplona Mariano, F.; Exel Santana, J.; Pereira Santiago, P. R. (Journal of Applied Biomechanics, 2016)
The aims of the current study were to analyze a kick from 10 m in a futsal context and the parameters of muscular strength using an isokinetic dynamometer in a laboratory environment, performed with the dominant (DL) and nondominant lower limbs (NDL). Seventeen professional elite players participated. Kicking performance was evaluated from the second penalty mark. Next, athletes completed a strength evaluation with an isokinetic dynamometer at speeds of 60°·s-1, 180°·s-1, and 300°·s-1. Significant differences were observed for hip (15.64 ± 3.44; 13.97 ± 2.62), ankle (63.19 ± 8.90; 52.55 ± 8.72), foot (82.31 ± 7.93; 68.41 ± 7.85), and ball (99.74 ± 8.45; 88.31 ± 7.93) speeds (km·h-1), and average power at 180°-s-1 (325.59 ± 40.47; 315.79 ± 39.49 W), but not for accuracy (1.33 ± 0.57; 1.66 ± 0.77 m) between the DL and NDL, respectively. Few moderate correlations were observed in the DL (r = .54-64) or NDL (r = .53-.55) between the kinematic variables of kick and muscular strength parameters (P < .05). We conclude that highly trained players present asymmetries in kicking motion; however, the imbalance in muscular strength is very small. We recommend that specific court tests be conducted to reliably characterize kicking performance in futsal. Success in kicking seems to be too variable and complex to be totally predicted only by joints, foot and ball speed, and lower limb muscular strength parameters. ABSTRACT FROM AUTHOR